Domestic versus international attack (terrorist) impact on the equity market: evidence from Iraq / Noorlina Amri - Amri, Noorlina (2016)
Purpose - The purpose of this paper is to study the costs or impacts of terrorist event of what it can do to the market to investors. Design / Methodology / Approach - This paper using study methodology, to test which attack does the affect more on the stock market of Iraq. Findings - The result show that stock market of Iraq affect more through to domestic attack compare to international attack for the one whole year of 2014. Paper type - Research paper